2019
DOI: 10.2217/fca-2018-0078
|View full text |Cite
|
Sign up to set email alerts
|

Tafamidis for the Treatment of Transthyretin Amyloidosis

Abstract: Transthyretin (TTR)-related cardiomyopathy is an underdiagnosed cause of heart failure but is increasingly recognised in various settings-from patients admitted with heart failure to symptomatic aortic stenosis-and is rapidly becoming the most frequent form of systemic amyloidosis. Following the recent publication of the landmark ATTRACT trial, that showed tafamidis to be the first treatment to improve survival in patients with TTR-related cardiac amyloidosis and heart failure, we reviewed the drug's rationale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The incidence of adverse events is similar in the tafamidis and placebo groups. 14 It stabilizes transthyretin tetramer by binding to the thyroxine-binding site of TTR tetramer and preventing dissociation of TTR tetramer into monomers, thus reducing TTR amyloid. 15 For the treatment of hereditary TTR amyloidosis, new therapies have been released.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of adverse events is similar in the tafamidis and placebo groups. 14 It stabilizes transthyretin tetramer by binding to the thyroxine-binding site of TTR tetramer and preventing dissociation of TTR tetramer into monomers, thus reducing TTR amyloid. 15 For the treatment of hereditary TTR amyloidosis, new therapies have been released.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was further referred for DNA analysis, which detected a Glu89Gln mutation in exon 3 of the TTR gene and the final diagnosis of ATTR was made. Treatment with the orphan drug tafamidis [7] was started and the patient currently shows no disease progression.…”
Section: Case Reportmentioning
confidence: 99%
“…Tafamidis is a non‐nonsteroidal anti‐inflammatory benzoxazole derivative that binds with high affinity and selectivity to TTR, stabilizing the TTR tetramer, arresting the amyloid cascade, and disrupting the progression of ATTR amyloidosis 9,10 . In a pivotal 18‐month, randomized, placebo‐controlled trial, tafamidis was shown to reduce neurologic deterioration, preserve nerve function, and maintain quality of life in patients with early‐stage ATTR‐PN 11,12 .…”
mentioning
confidence: 99%
“…8 Tafamidis is a non-nonsteroidal anti-inflammatory benzoxazole derivative that binds with high affinity and selectivity to TTR, stabilizing the TTR tetramer, arresting the amyloid cascade, and disrupting the progression of ATTR amyloidosis. 9,10 In a pivotal 18-month, randomized, placebo-controlled trial, tafamidis was shown to reduce neurologic deterioration, preserve nerve function, and maintain quality of life in patients with early-stage ATTR-PN. 11,12 Evidence from the clinical development program, including open-label extension studies providing data from up to 6 years of treatment, and large registry and referral center studies, providing real-world data from up to 10 years, supports the longterm safety and effectiveness of tafamidis in delaying neurologic deterioration and prolonging survival in ATTR-PN.…”
mentioning
confidence: 99%